Исследование термической устойчивости хлорокобальтатов (II) аммония; Журнал неорганической химии; Т. 59, вып. 6 - Жилина О. В. Ольга Владимировна; Дьяченко А. Н. Александр Николаевич; Козик В. В. Владимир Васильевич; Крайденко Р. И. Роман Иванович (2014, 2014)
Заглавие с экрана